2019
DOI: 10.17269/s41997-019-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

Age, period, and cohort effects for future employment, sickness absence, and disability pension by occupational gender segregation: a population-based study of all employed people in a country (> 3 million)

Abstract: Objectives The occupational gender segregation of the labour market is very strong, both in Sweden and in North America. Nevertheless, there is little knowledge on how this is associated with employees' future employment or morbidity. The objectives of this study were to explore age, period, and cohort effects on future employment and morbidity in terms of sickness absence (SA) or disability pension (DP) among women and men employed in numerically gender-segregated or gender-integrated occupations. Methods Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…However, we found that women’s SA prevalence was higher in all six branches of industry. Some studies have found that being the minority sex in a highly sex-segregated occupation is associated with higher risk of SA [ 23 ]. For both women and men, the branch of industry with the highest SA prevalence was care and education, and women did not have higher SA prevalence in manufacturing or construction, comprising many numerically male-dominated occupations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that women’s SA prevalence was higher in all six branches of industry. Some studies have found that being the minority sex in a highly sex-segregated occupation is associated with higher risk of SA [ 23 ]. For both women and men, the branch of industry with the highest SA prevalence was care and education, and women did not have higher SA prevalence in manufacturing or construction, comprising many numerically male-dominated occupations.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of the papers measured different variables pre-and post-implantation. Some papers reported that implantation had (self-rated) positive impacts on income, employment status, job satisfaction, professional skills, development in professional careers, employment opportunities, position in the labour market and how much the individuals were able to work (Clinkard et al 2015;Fazel and Gray 2007;Goh et al 2016;Kos et al 2007;Huarte et al 2017;Harkonen et al 2017). Others revealed the impact CIs had on performances in WL, such as improved communication with co-workers, phone abilities, increased awareness of warning signals and other sounds in the environment, and overall increased functioning (Kos et al 2007;Harkonen et al 2015b;Saxon et al 2001).…”
Section: Cochlear Implants and Working Lifementioning
confidence: 99%
“…Women’s experiences of pregnancy, their perceptions about job demands, and their attitudes to SA during pregnancy may be sensitive to the culture and the norms of their occupation [13, 14]. An increasing number of studies document an association between the numerical gender composition, i.e., the proportion of women and men, in an occupation and SA [1522]. Based on Kanter’s theory of tokenism [15, 23], gender-minority groups in an occupation have been hypothesized to have higher SA than the majority due to the minority position being associated with higher stress and lower social resources, and subsequently poorer health and lower motivation to go to work [15, 23].…”
Section: Introductionmentioning
confidence: 99%